Game Promosi Wisata Kota Malang “Kakang Mbakyu” Dengan Menggunakan Decission Tree dan Hierarchy Finite State - Fathurrahman; Yunifa Miftachul Arif (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2020)
Currently, the Tourism Sector in Indonesia is considered the most effective sector contributing to increasing the country's foreign exchange, Foreign exchange earnings were obtained from Indonesian tourism visits which surged and recorded as the highest compared to other countries in Southeast Asia, In particular in the city of Malang there was a significant increase in the number of tourists, based on data listed at www.malangkota.go.id in 2015 the number of tourists entering the city of Malang totaled 3,290,067 people, while 8,265 foreign tourists visited the following year to 3,987,074 for domestic tourists and 9,535 foreign tourists. In this research, Decission Tree algorithm was successfully implemented in the game by producing a time variable gain with a value of 2.01 and a gain point of 1.86 so that the time variable will be processed before the variable points to produce level jumps according to the ability of the player, and for the Hierarchy Finite State Machine, it proved to be successful with the NPC's moving behavior in accordance with the previously designed rules.